Implikatur Percakapan dalam Komunikasi Interpersonal Orang Tua Terhadap Anak di Usia Remaja - Sugrahita Harja Susetya, Domas; Mariyatus Zakiyah, Ainaiyah (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2020)
ABSTRACT In a conversation, there is not rarely a speech that contains an unspoken meaning, namely the meaning hidden behind the speech, thus making the speech partner have difficulty in understanding the meaning of speech. The meaning of the speech that is not spoken here, is called (conversational implicature). Usually the difficulties in understanding the meaning of the speech are contained in general conversations. It's different from conversations that happen in a family environment. Conversations that exist in the family environment is a form of daily conversation, where between speakers and speech partners already have each other experience and background knowledge called as a pregmatic context, so that the conversations in the family can run smoothly. Therefore, the purpose of creating this article is to understand about the implications of conversation in interpersonal communication of parents towards children in adolescence, so that with the understanding of the implications of this conversation, it can improve the communication process. Keywords: Conversational implications, interpersonal communication, pregmatic context, speech situations.